Regulation of skeletal muscle phosphorylase phosphatase activity. I. Kinetic properties of the active and inactive forms - Torres, H.N. (1970)
1. 1. The inactivation of phosphorylase a phosphatase decreased the maximum velocity of the phosphorylase a to phosphorylase b conversion reaction when it was assayed at different phosphorylase a concectrations. 2. 2. Maximal phosphorylase a phosphatase activities were found between pH 8 and 8.3. Inactivation of the phosphorylase a phosphatase led to a decrease in the activity in all the pH ranges tested. 3. 3. Theophylline and caffeine stimulated the phosphorylase a phosphatase. The effect of these substances was exerted in the reaction assay of the enzyme. 4. 4. ATP, ADP, AMP, GTP, UTP, CTP and pyrophosphate were found to decrease the rate of the reaction catalyzed by phosphorylase a phosphatase. This effect showed a striking parallelism with the capacity of these compounds to stimulate the phosphatase inactivation. © 1970.